2009
DOI: 10.1016/j.bpj.2009.08.030
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Spontaneous Ca2+ Oscillations in Astrocytes Mediated by Voltage-Gated Calcium Channels

Abstract: The purpose of this computational study was to investigate the possible role of voltage-gated Ca(2+) channels in spontaneous Ca(2+) oscillations of astrocytes. By incorporating different types of voltage-gated Ca(2+) channels and a previous model, this study reproduced typical Ca(2+) oscillations in silico. Our model could mimic the oscillatory phenomenon under a wide range of experimental conditions, including resting membrane potential (-75 to -60 mV), extracellular Ca(2+) concentration (0.1 to 1500 muM), te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 54 publications
1
49
0
1
Order By: Relevance
“…Astrocytes in rat brains expressed mainly the type 2 IP 3 Rs (Sharp et al, 1999;Holtzclaw et al, 2002). Recently, an empirically based model has been proposed for this particular IP 3 Rs isoform (Tu et al, 2005a,b), which seems very useful to portray Ca 2þ signaling in astrocytes (Lavrentovich & Hemkin, 2008;Zeng et al, 2009). In spite of the accuracy of these latterly proposed models for type 2 IP 3 Rs, it is our believe that the Li-Rinzel's simplified model not only captures the most important characteristics in the kinetics of the IP 3 R, but also can be directly interpreted in terms of molecular transitions in the receptor states (i.e., the subunits).…”
Section: Modeling the Spontaneousmentioning
confidence: 99%
See 3 more Smart Citations
“…Astrocytes in rat brains expressed mainly the type 2 IP 3 Rs (Sharp et al, 1999;Holtzclaw et al, 2002). Recently, an empirically based model has been proposed for this particular IP 3 Rs isoform (Tu et al, 2005a,b), which seems very useful to portray Ca 2þ signaling in astrocytes (Lavrentovich & Hemkin, 2008;Zeng et al, 2009). In spite of the accuracy of these latterly proposed models for type 2 IP 3 Rs, it is our believe that the Li-Rinzel's simplified model not only captures the most important characteristics in the kinetics of the IP 3 R, but also can be directly interpreted in terms of molecular transitions in the receptor states (i.e., the subunits).…”
Section: Modeling the Spontaneousmentioning
confidence: 99%
“…Previous studies have also demonstrated the existence of voltage-gated and ligand/storeoperated forms of active influxes. For example, different types of voltage-dependent Ca 2þ channels have been found in astrocytes (D'Ascenzo et al, 2004), a mechanism that was contemplated in a recent theoretical model (Zeng et al, 2009). However, blocking these voltage-gated Ca 2þ channels has produced different effects on the SCOs in astrocytes (Parri et al, 2001;Aguado et al, 2002;Wang et al, 2006b).…”
Section: A Passive/active Ca 2þ Entry From the Extracellular Spacementioning
confidence: 99%
See 2 more Smart Citations
“…Previous researcher have studied the effect of rapid and excess buffers on cytosolic calcium concentration in nerve cells like neuron, astrocytes, fibrocytes etc [3,4,5,9,10,12,15,17,19,21]. Calcium kinetics in nerve cells is governed by a set of reaction-diffusion equations which can be framed assuming the following bimolecular reaction between [Ca 2+ ] and buffer species [11,12]:…”
Section: Calcium Bufferingmentioning
confidence: 99%